Standar kompetensi pustakawan sebagai instrumen asesmen jabatan fungsional pustakawan - Amrullah Hasbana (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2017)
This paper describes some of the competencies that must be possessed by a librarian as a profession-al. Some of these competencies must reflect qualifications, competencies and performance in accor-dance with the policy and management of the Civil State Apparatus (ASN). Competencies owned by librarians will serve as the basis of consideration, assessment, to provide promotion or promotion to acquire a step to higher positions. Competence is not only related to the ability to carry out the main tasks and functions of librarians as set forth in the regulation, Permenpan RB No. 9 of 2014 Sec-tion 4 which is referred to as competence relating to performance indicators, but must be supported also by other competencies such as interpersonal skills that include adaptability, communication and advocacy, negotiation, change management, decision making, problem solving, high initiative, innovation and collaboration and leadership competence, leadership.